Social policy, psychology and climate mitigation - Can Karaarslan (Hochschule Offenburg, Fakultät Medien, 2022)
The present essay discusses several channels of social policy on climate mitigation and utilizes the Universal Basic Income (UBI) scheme as an example for endowment increasing and inclusive social policy instruments. UBI comprises the payment of a fixed amount of money to every member of a society from birth to death and is not bounded to any precondition. It is expected to increase resilience of individuals against disruptive and unexpected processes, such as climate change, digitization, aging population and the changing world of work, rather than particular life-trajectories. UBI is found to be a social policy instrument whose effects can contribute to climate mitigation. This essay is far from being conclusive and rather aims to raise questions which require further analysis.
urn:nbn:de:bsz:ofb1-opus4-58085
Keywords: 650; Climate mitigation; Social policy; Universal Basic Income